Information Security and Cryptology 8th International Conference, Inscrypt 2012, Beijing, China, November 28-30, 2012, Revised Selected Papers - Kutylowski, Miroslaw; Yung, Moti (Security and Cryptology, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International Conference on Information Security and Cryptology, Inscrypt 2012, held in Beijing, China, in November 2012. The 23 revised full papers presented were carefully reviewed and selected from 71 submissions. The papers cover the topics of side channel attacks, extractor and secret sharing, public key cryptography, block ciphers, stream ciphers, new constructions and protocols.